Controlled release of 5-aminosalicylicacid from chitosan based pH and temperature sensitive hydrogels - PEKER, İSMAİL; EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (ELSEVIER SCIENCE BV, 2013)
A series of temperature and pH responsive hydrogels based on chitosan and poly(N-isopropyl acrylamide) (PNIPA) was prepared by redox polymerization. Effect of the composition on swelling behavior of the hydrogels and the release of 5-aminosaylcilic acid (5-ASA) at different temperatures and pHs have been investigated. Ammonium persulphate and TEMED were used as a redox pair at room temperature. As a cross linker, methacrylated chitosan was synthesized through the reaction of chitosan with glycidyl methacrylate (GMA). Introduction of the cross-linker provided the hydrogels with pH and temperature sensitivities. The phase transition temperatures of the hydrogels were determined by derivative differential scanning calorimeter (DDSC). Their phase transition temperatures were increased by chitosan content. Swelling behaviors and the release of 5-ASA varied significantly with pH, temperature and the gel composition. The release of 5-ASA from the hydrogels was followed by UV-Vis and fluorescence spectroscopy. Crown Copyright (c) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: Chitosan; NIPA; Hydrogel; 5-ASA; Drug release; DRUG-DELIVERY; GENE DELIVERY; PHYSICOCHEMICAL PROPERTIES; BLEND FILMS; ACID; BIOCOMPATIBILITY; COMPLEX; CARRIER